Adipose-derived stem cell exosomes suppress NLRP3-mediated neuronal pyroptosis to attenuate seizures in a kainic acid-induced temporal lobe epilepsy model - Ding, Siqi; Chen, Wanying; E., Yajun; Zhou, Jinli; Zhao, Songyun; Chen, Yanming; Dong, Zhewei; Dai, Hao; He, Yucang (Frontiers in Immunology, 2025)
BackgroundPyroptosis-mediated neuroinflammation represents a critical pathological mechanism in drug-resistant temporal lobe epilepsy (TLE), while Adipose-derived stem cell exosomes (ADSC-Exos) may target this process through NLRP3 inflammasome inhibition. Our study investigated the therapeutic effects of ADSC-Exos by mitigating NLRP3-driven pyroptosis in TLE.MethodsWe isolated ADSC-Exos, the characteristics of which were confirmed. The Kainic acid-induced mouse TLE model were used to assess the in vivo effect of ADSC-Exos. To evaluate ADSC-Exos penetration, brain tissues were collected for fluorescence quantification. TUNEL and Nissl staining were used to evaluate hippocampal neuronal damage. Pyroptosis markers were detected by Western blot, qRT-PCR, and immunofluorescence. Bioinformatics analysis was performed to explore potential miRNAs in ADSC-Exos that might contribute to their therapeutic effects.ResultsIntravenously injected ADSC-Exos efficiently crossed the blood-brain barrier, peaking in brain accumulation at 4 hours post-administration. Treatment with ADSC-Exos resulted in a 48.9% reduction in seizure duration (p<0.0001) and a 42% reduction in spontaneous recurrent seizure frequency (p<0.0001) in temporal lobe epilepsy. Furthermore, ADSC-Exos exhibited significant neuroprotection while suppressing key pyroptosis-related proteins, including NLRP3, Caspase-1, GSDMD, and IL-1β. Bioinformatics analysis further identified 16 candidate miRNAs in ADSC-Exos potentially mediating these therapeutic effects.ConclusionsADSC-Exos exert neuroprotective effects in temporal lobe epilepsy in association with regulation of the NLRP3-associated pyroptosis pathway, thereby suppressing neuroinflammation and neuronal death, highlighting their potential therapeutic value.